Delayed diagnosis of human immunodeficiency virus infection in people diagnosed with syphilis: A nationwide cohort study from 2011 to 2018 in Japan. Issue 2 (February 2022) - Naito, Toshio; Fujibayashi, Kazutoshi; Mori, Hirotake; Fukushima, Shinichi; Yuda, Mayumi; Fukui, Nobuyuki; Tsukamoto, Shotaro; Suzuki, Mai; Goto-Hirano, Keiko; Kuwatsuru, Ryohei
Abstract: Early treatment of HIV infection depends on timely diagnosis, but many persons living with HIV/AIDS (PLWHA) are unaware of their infection. Though many patients seeking medical attention for sexually transmitted diseases have HIV, many patients' HIV co-infection is undiagnosed in Japan. This is the first report to analyze the timing of syphilis infection in PLWHA of all ages through the use of the National Database of Health Insurance Claims and Specific Health Checkups of Japan (NDB), containing clinical data of the largest group of HIV-positive patients available in Japan. Overall, 1521 PLWHA (male 93.2%) newly diagnosed and started on antiretroviral therapy were identified in 2016, and 646 (42.5%) patients had a diagnosis of syphilis between 2011 and 2018. Although 100 patients were diagnosed with syphilis before their HIV diagnosis, only 17 (17.0%) had been tested for HIV. Over 50 patients per year became infected with syphilis even after their HIV diagnosis (2017, n = 65 (4.3%); 2018, n = 58 (3.8%)). Although early diagnosis of HIV infection is important, most syphilis patients in Japan had not been properly tested for HIV infection. Since a certain number of HIV patients developed syphilis after HIV diagnosis, education for newly diagnosed HIV patients is important.